Alfabetização científica e tecnológica por meio de uma sequência didática interdisciplinar sobre o Ribeirão Santa Rita - Silva, Priscila Machado da (Universidade Federal de São Carlos, 2022)
One of the natural goods that is born and cuts through the city of Fernandópolis/SP is the Ribeirão Santa Rita, which, despite starting in this municipality, only ends when it flows to the waters of Rio Grande that divides the states of São Paulo and Minas Gerais. Thus, based on science and technology that is present in the daily of the whole society, this present work aims to investigate how a regional theme (Ribeirão Santa Rita) can contribute to promote the Scientific and Technological Literacy of high school students, through a didactic sequence. Thus, through dissemination on social networks, students went invited to participate in the "Workshop on Science and citizenship: Ribeirão Santa Rita", that happened remotely. This workshop was structured using an interdisciplinary didactic sequence based on the three pedagogical moments. It was evaluated about the Scientific and Technological Literacy of the students, using the Discursive Textual Analysis, so that the corpus selected for the analysis was categorized according to historical context of the city, relationship with everyday life, health and environment, business interests and theoretical concepts. Subsequently, it was evaluated each of these categories according to the criteria of ACT proposed for Bocheco (2011). In this way, it was possible to verify that the workshop contributed to the Pratical, Civic and Professional or Economical Scientific Literacy of the students. The category where Bocheco's (2011) indicator were less evident was: "historical context of the city", while in the "health and environment" category, the Civic Scientific Literacy indicator showed great evidence.
Scientific and technological literacy through an interdisciplinary didactic sequence about the Ribeirão Santa Rita
Keywords: Temas regionais; Sequência didática; Alfabetização científica e tecnológica; Regional themes; Didactic sequence; Scientific and technological literacy; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM